Phosphorescent mono- and diiridium(III) complexes cyclometalated by fluorenyl- or phenyl-pyridino ligands with bulky substituents, as prospective OLED dopants - M’hamedi, Ahmed (Acta Crystallogr E Crystallogr Commun, 2020)
The crystal structures of tris[9,9-dihexyl-2-(5-methoxypyridin-2-yl-κN)-9H-fluoren-3-yl-κC (3)]iridium pentane monosolvate, [Ir(C(31)H(38)NO)(3)]·C(5)H(12), (I), di-μ(2)-chlorido-bis{bis[2-(5-fluoropyridin-2-yl)-9,9-dihexyl-9H-fluoren-3-yl]iridium} pentane 0.3-solvate, [Ir(2)(C(30)H(35)FN)(4)Cl(2)]·0.3C(5)H(12), (II), di-μ(2)-cyanato-bis{bis[9,9-dihexyl-2-(5-methoxypyridin-2-yl)-9H-fluoren-1-yl]iridium} pentane monosolvate, [Ir(2)(C(31)H(38)NO)(4)(NCO)(2)(NCO)(2)]·C(5)H(12), (III), and {μ-N,N′-bis[3,5-bis(trifluoromethyl)phenyl]oxamidato}bis(bis{2-[4-(2,4,6-trimethylphenyl)pyridin-2-yl]phenyl-κ(2) C (1),N′}iridium)–chlorobenzene–pentane (1/2.3/0.4), [Ir(2)(C(20)H(19)N)(4)(C(18)H(6)F(12)N(2)O(2))]·2.3C(6)H(5)Cl·0.4C(5)H(12), (IV), synthesized in the quest for organic light-emitting devices, were determined. The bis-μ(2)-chloro and bis-μ(2)-cyanato complexes have ΔΔ and ΛΛ configurations of the distorted octahedral Ir centres in racemic crystals, whereas the oxamido complex has a centrosymmetric (meso) structure with the ΔΛ configuration. The bridging oxamido moiety has a nearly planar anti geometry. All structures show substantial disorder of both host molecules and solvents of crystallization.